2000
DOI: 10.1002/1529-0131(200009)43:9<1982::aid-anr9>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of autoantibodies against the phosphatidylserine–prothrombin complex with manifestations of the antiphospholipid syndrome and with the presence of lupus anticoagulant

Abstract: Antiprothrombin antibodies are heterogeneous and their clinical relevance depends on the method of detection applied. Positive results on the aPS/PT test can serve as a marker of thrombotic events in patients with autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
222
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 299 publications
(237 citation statements)
references
References 34 publications
8
222
1
6
Order By: Relevance
“…We have reported the detection of APS/PT and have shown that the results obtained depend closely on the assay performed (37). The presence of APS/PT, but not APT-A, correlated significantly with the clinical manifestations of antiphospholipid syndrome (OR 8.29, 95% CI 3.03-22.71, P Ͻ 0.0001 versus OR 1.89, 95% CI 0.71-5.06, P not significant).…”
Section: Clinical Significance Of Aptsmentioning
confidence: 87%
See 2 more Smart Citations
“…We have reported the detection of APS/PT and have shown that the results obtained depend closely on the assay performed (37). The presence of APS/PT, but not APT-A, correlated significantly with the clinical manifestations of antiphospholipid syndrome (OR 8.29, 95% CI 3.03-22.71, P Ͻ 0.0001 versus OR 1.89, 95% CI 0.71-5.06, P not significant).…”
Section: Clinical Significance Of Aptsmentioning
confidence: 87%
“…Our group (37) recently reported that the detection of APS/PT strongly correlated with the presence of LAC. Most investigators have used only the APT-A ELISA, presuming that both systems of detection (APT-A and APS/PT ELISAs) detect the same antibodies.…”
Section: Antiprothrombin Antibodiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, autoantibodies for prothrombin as well as beta 2-GPI aCL have been shown to be associated with LA (1,2), and IgG phosphatidylserine-dependent antiprothrombin antibodies (aPS/PT) were also reported to be strongly associated with LA (3) T a b l e 1 . B a s e l i n e Ch a r a c t e r i s t i c s a n d F e a t u r e s o …”
Section: Antiphospholipid Syndrome (Aps) An Autoimmune Disease Definmentioning
confidence: 99%
“…The serological markers for this syndrome are antiphospholipid antibodies (aPLs), such as the lupus anticoagulant (LA), anti-cardiolipin antibody (aCL) 5,6 , antibody against anticardiolipin β 2 -glycoprotein I complex antibody (CL/β 2 GPI), and anti-phosphatidylserine-prothrombin complex antibody (aPS/PT) 7,8 . aPLs are frequently found in patients with systemic autoimmune diseases, especially in systemic lupus erythematosus (SLE).…”
Section: Introductionmentioning
confidence: 99%